(untitled) (Journal of Health, Population and Nutrition, 2009)
The transgender people (hijra), who claim to be neither male nor female, are socially excluded in Bangladesh. This paper describes social exclusion of hijra [The term is used in this abstract both in singular and plural sense] focusing on the pathway between exclusion and sexual health. In an ethnographic study, 50 in-depth interviews with hijra, 20 key-informant interviews, and 10 focus-group discussions (FGDs), along with extensive field observations, were conducted. The findings revealed that hijra are located at the extreme margin of exclusion having no sociopolitical space where a hijra can lead life of a human being with dignity. Their deprivations are grounded in non-recognition as a separate gendered human being beyond the male-female dichotomy. Being outside this norm has prevented them from positioning themselves in greater society with human potential and security. They are physically, verbally, and sexually abused. Extreme social exclusion diminishes self-esteem and sense of social responsibility. Before safer sex interventions can be effective in a broader scale, hijra need to be recognized as having a space on society’s gender continuum. Hijra, as the citizens of Bangladesh and part of society’s diversity, have gender, sexual and citizenship rights, that need to be protected. Key words: Hijra; HIV; Social exclusion; Bangladesh doi: 10.3329/jhpn.v27i4.3388 J Health Popul Nutr 2009 Aug;27(4):441-451